2008
DOI: 10.1080/01443610802196658
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal multivitamins containing folic acid do not decrease prevalence of depression among pregnant women

Abstract: Several studies have reported an association between depression and folic acid deficiency. We investigated whether intake of prenatal multivitamins containing folic acid (MVandFA) was associated with decreased rates of depression among pregnant women. A questionnaire was given to 1,314 low-risk pregnant women. Of them, 1,277 (97.2%) women completed the questionnaire. The overall prevalence of depression was 8.1%. Of 652 participants who did not take MVandFA, 9.4% had depression, whereas 6.9% of 624 women who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Patients receiving the active treatment had significantly lowered Hamilton Rating Scale for Depression (HAM-D) scores and significantly higher rates of response and remission at weeks 6 and 8. In Korea, Cho et al31 utilized a questionnaire format with 1,314 pregnant women. This group found a trend for Folic Acid (FA) and Multivitamins (MVA) protecting against AD, but the relationship was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Patients receiving the active treatment had significantly lowered Hamilton Rating Scale for Depression (HAM-D) scores and significantly higher rates of response and remission at weeks 6 and 8. In Korea, Cho et al31 utilized a questionnaire format with 1,314 pregnant women. This group found a trend for Folic Acid (FA) and Multivitamins (MVA) protecting against AD, but the relationship was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…This prospective cohort study of 865 pregnant women found no evidence of an association; however, the number of women classified as depressed was relatively small (14%) considering that a threshold of 9 or more on the Edinburgh Postnatal Depression Scale (EPDS) was used, and folic acid supplementation was not included in the analysis (Miyake et al, 2006). Cho et al (2008) investigated whether intake of prenatal multivitamins containing folic acid was associated with decreased rates of depression among 1277 pregnant women. The overall prevalence of depression was 9.4% among those taking multivitamins and 6.9% among those not taking multivitamins, but the study did not show strong evidence of an effect (P ¼ 0.11).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in depression screening tool (Kessler Psychological Distress Scale versus EPDS) and time of sample collection (antepartum versus postpartum) may explain the divergent results observed in the two studies. Other signi cant studies exploring the association between B-vitamin and PPD measured only dietary intake of folate, vitamin B6 and B12 (25) or supplementation (26)(27)(28) without measuring the circulating levels of vitamin B12 (29)(30)(31) . We conducted a pilot study to observe the status of vitamin B12, total folate and hcy in 24-48 hours post delivery, and found higher hcy levels in depressed women when compared to the non-depressed.…”
Section: Discussionmentioning
confidence: 99%